2020
DOI: 10.2196/17939
|View full text |Cite
|
Sign up to set email alerts
|

Computer-Based Stratified Primary Care for Musculoskeletal Consultations Compared With Usual Care: Study Protocol for the STarT MSK Cluster Randomized Controlled Trial

Abstract: Background Musculoskeletal (MSK) pain is a major cause of pain and disability. We previously developed a prognostic tool (Start Back Tool) with demonstrated effectiveness in guiding primary care low back pain management by supporting decision making using matched treatments. A logical next step is to determine whether prognostic stratified care has benefits for a broader range of common MSK pain presentations. Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 68 publications
0
20
0
Order By: Relevance
“…• WP3 -pilot/feasibility cluster randomised controlled trial of stratified care in general practice [15,16] • WP4 -main cluster randomised controlled trial of stratified care in general practice [17] packages (see Table 1,below). Several of the studies from these work packages have previously been published in this journal [4,15,16].…”
Section: The Start Msk Research Programmementioning
confidence: 99%
See 1 more Smart Citation
“…• WP3 -pilot/feasibility cluster randomised controlled trial of stratified care in general practice [15,16] • WP4 -main cluster randomised controlled trial of stratified care in general practice [17] packages (see Table 1,below). Several of the studies from these work packages have previously been published in this journal [4,15,16].…”
Section: The Start Msk Research Programmementioning
confidence: 99%
“…Final results of the clinical trial are yet to be published. The stratified care intervention is described in detail elsewhere [12,17] and comprises two components: the use of the prognostic risk tool (Keele STarT MSK Tool) and the selection of an appropriate clinical treatment, matched to the patient's prognostic risk group. In brief, the key components for intervention practices were: • To ensure that the GP engages with the EHR to trigger the stratified care template whilst the patient is still present…”
Section: The Start Msk Research Programmementioning
confidence: 99%
“…The strati ed care intervention is described in detail elsewhere [14,17] and comprises two components: the use of the prognostic risk tool (Keele STarT MSK Tool) and the selection of an appropriate clinical treatment, matched to the patient's prognostic risk group. In brief, the key components for intervention practices were:…”
Section: The Start Msk Research Programmementioning
confidence: 99%
“…Also, we identified one published pilot study and protocol for a trial testing stratified care in musculoskeletal conditions including OA. 39 , 40 No trials or protocols were identified on head-to-head comparisons of stepped and stratified models of care. Although there is limited research to inform whether models of care could be the same for OA and LBP or if one model should be chosen rather than the other, a recent focus group study indicated that practitioners consider a generic stratified model to be relevant across 5 musculoskeletal conditions.…”
Section: Key Message #2: It Is Not a Choice Between Stepped Care Omentioning
confidence: 99%